East Asian expatriate football players and national team success: Chinese, Japanese, and South Korean players in Europe (2000–2024) - Le Luo; Yangke Tang; Xiaohan Li; Ge Sun; Enkai Guo; Hanbing Xu (Scientific Reports)
Abstract This study investigated the influence of Chinese, Japanese, and South Korean football players’ participation in European leagues on their national teams’ FIFA rankings from 2000 to 2024. Utilizing data from 22,972 matches featuring 392 players across 36 European leagues and 12 tournaments or cup competitions, survival and conditional process analyses were conducted to explore the relationships between expatriate player counts, appearances, playing time, and FIFA rankings. The results demonstrated a significant correlation between the number of expatriate players, particularly in top-tier leagues, and national team rankings. Notably, Japanese and South Korean players exhibited longer durations of participation and higher rates of advancement to elite European leagues compared to Chinese players. Furthermore, the conditional process analysis revealed an indirect effect of expatriate player count on FIFA rankings, mediated by increased appearances and playing time, with the strongest influence observed in the Big Five leagues. These findings underscore the importance of international exposure for advancing East Asian football and provide insights for policymakers on effectively nurturing young talents for international careers.